ANALISIS KEAMANAN SIBER DAN HUKUM DARI PERSPEKTIF GENDER DAN FILSAFAT POLITIK ALISON M. JAGGAR - Alfonso Munte (Al-Adl : Jurnal Hukum, 2021)
The policy for increasing sensitivity, awareness, and problem solving for women, youth, and children has been in the works for a long time. This virtue in affirming the rights of women, youth, and children has made it a global issue.  This grand idea has earned a stage in the community and institutions in the world. Unfortunately, in the negotiation process, they are weak and weakened. Often they do not get involves in the process of policies making and legislation especially in cybersecurity, the law of security, accessibility to cybersecurity, and the law. Therefore, based on the imbalance mentioned, the issue formulated, do the policymaker of cybersecurity law question the experience and identity of women in legal texts? How can this be possible? This article tries to analyze cybersecurity and legal struggles from Alison M. Jaggar's political philosophy and then analyzes dialectically with Feminist Legal Analysis to save women, adolescents, and children from exploitation in cyberspace. The method used in this research is a literature study. Based on the descriptive results of the data, I find that it is difficult until today for women to achieve justice in legal processes related to cyber violence.